Ethical Practices in Information Service Provision at Makerere University Business School Library Uganda - Nambobi, Olivia; Kaddu, Sarah; Bwengye, Michael M. M. S.; Tusiime, Olive (International Journal for Multidisciplinary Research, 2023)
Ethical practice in information service provision involves choice of material, access, equality of treatment, copyright, intellectual freedom, protecting user’s rights, confidentiality, and, avoiding concealment of information, misinforming clients and divulging private information. The rationale of this study was to find out whether MUBS librarians are aware of these ethical practices and apply them in the performance of services’ provision to their clients. The study examined librarians’ ethical practices in the provision of information services at Makerere University Business School library. It was guided by the following specific objectives: i)(i) To identify the range of information services provided by MUBS library. ii) To explore the core principles and ideals that underpins ethical practices in MUBS library. iii) To determine the implications of ethical dilemmas on provision of information services in MUBS library. iv) To suggest an ethical model of practice for delivering information services in MUBS library, Uganda. Descriptive research design was adopted with a qualitative research approach. A purposive sampling technique was preferred. The sample size comprised of 54 informants including MUBS Library staff, MBA students, Administrative staff and lecturers. Document review, observation, face to face interviews and self-administered questionnaires were the methods used in the collection of data. Services provided were photocopy, printing and scanning (67.6%); direct personal assistance to readers seeking information (64.8%); printed books long term loan (1-2 weeks)(64.7%) and user education (55.9%). Reading and discussion space (58.8%) available were satisfactory environmental conditions. Information ethics was integrated in library professional practice in MUBS library especially from the scope of PAPA model. The implications of ethical dilemmas on provision of information services: there were several factors beyond those in the PAPA model and WSIS Action Line 10 that influence information ethical practice by library professionals in MUBS library. These factors included; limited number of qualified staff in MUBS Library; inequalities in internet access; lack of awareness and interest in having the code; lack of locally developed code of ethics and challenge of implementing international codes of ethics; low level of enforcement of ethical conducts by library management; unpopularity of ethical code;